'The Consent of the Faithful' from 1 Clement to the Anglican Covenant. Issue 1 (29th October 2012) - King, Benjamin J.
Abstract The origins of the term consensus fidelium lie in the rhetorical tropes of pagans who exhorted unity between friends and within cities – tropes supporting the hierarchy of imperial elites. The earliest Christians adapted this language for the same purpose within churches: to speak of unity and lay involvement in support of Church hierarchy. After the Reformation, Church of England writers used this rhetoric to enforce conformity to church polity and morality. The Tractarians and their successors employed a rhetorical 'voice of the laity' as a bolster for episcopal power. While the early twentieth century saw some in the Church of England and Anglican Communion use this same rhetoric to bring the laity into actual decision-making processes, the rhetoric of recent statements by the Communion has left power firmly with bishops.